The Effects of Perilla frutescens Extracts on IgA Nephropathy: A Systematic Review and Meta-Analysis - Gigi Adam; Ana-Maria Adam; Silvia Robu; Valeriu Harabor; Anamaria Harabor; Aurel Nechita; Denisa Batir Marin; Ionela-Daniela Morariu; Oana Cioanca; Ingrid-Andrada Vasilache; Monica Hancianu (MDPI AG, 2023)
(1) Background: Chronic renal disorders (CRD) are associated with significant comorbidities and necessitate complex therapeutic management. As time passed, Perilla frutescens (PF) became a promising therapeutic option for CRD. The aim of this systematic review and meta-analysis was to outline the therapeutic effects of PF extracts on various models of immunoglobulin a (IgA) nephropathy; (2) Methods: Medline, Embase, and Cochrane databases were used to find relevant studies. All prospective interventional studies that evaluated the effect of PF extract versus placebo on rat models of chronic renal disorders were assessed according to the international guidelines; (3) Results: Our search yielded 23 unique records, out of which only five were included in the analysis. Our results showed that administration of PF extracts led to a statistically significant reduction in proteinuria and PCNA levels in rats that received high doses of the extract as well as in the PCNA level and DNA synthesis in rats that received low doses of the extract. The evaluated outcomes benefited from a low degree of heterogeneity; (4) Conclusions: Some of the evaluated outcomes were significantly reduced by both high and low doses of extracts from Perilla frutescens. Further studies are needed to determine the exact effect over IgA nephropathy in human subjects.